Effect of seeding rates of oats (Avena sativa L.), wheat (Triticum aestivum L.) and common vetch (Vicia sativa L.) on the yield, botanic composition and nutritive value of the mixture - Castro M.P.; Piñeiro J.; Sau F. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Seven seeding rates were sown, ranging from oats and wheat monoculture (300-0) to vetch monoculture (0-300), following a changing series scheme, with a total (cereal plus vetch) of 300 viable seeds m-2 as objective in each treatment. Yield was measured in April 1998 with the oats at heading, wheat at beginning of heading, and the vetch at preflowering stage. Botanical analysis showed more weeds in the vetch and cereal monoculture plot and more vetch in the wheat-vetch mixtures. The increase of the relative number of vetch seeds at sowing lead to highly significant decreasing yields harvested that were 9, 7 and 4 t per ha of dry matter for oats, wheat and vetch monoculture respectively, more crude protein content (8 and 12 to 20 for oats, wheat and vetch monocultures), and highly significant decrease of acid and neutral detergent fibers and organic matter contents.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)